Vzdělávání zaměstnanců státní správy v oblasti kybernetické bezpečnosti - Vondráčková, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce řeší problematiku vzdělávání zaměstnanců státní správy v oblasti kybernetické bezpečnosti. Cílem je analyzování současného stavu bezpečnostního povědomí ve státní organizaci a vytvoření konceptu vzdělávání zaměstnanců. Teoretická část je věnována teoretickým východiskům, zahrnujícím terminologii, aktuální legislativě a metodice budování bezpečnostního povědomí. Analytická část se věnuje současnému stavu vzdělávání zaměstnanců v oblasti kybernetické a informační bezpečnosti. Vlastní řešení obsahuje návrh konceptu vzdělávání, které zohledňuje současný stav a potřeby organizace v kontextu aktuálních bezpečnostních hrozeb.

This diploma thesis addresses the issue of employee training in the state administration in the field of cybersecurity. The goal  is to analyze the current state of security awareness within a state organization and to propose a concept for employee training. The theoretical part is dedicated to theoretical foundations, including terminology, current legislation, and the methodology for building security awareness. The analytical part focuses on the current state of employee training in the field of cybersecurity and information security. The proposed solution includes a training concept that takes into account the current state and needs of the organization in the context of current security threats.
Training of state administration employees in the field of cyber security
Keywords: kybernetická bezpečnost; informační bezpečnost; vzdělávání; budování bezpečnostního povědomí; státní správa; cybersecurity; information security; training; building security awareness; state administration